PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN KEPALA SEKOLAH TERHADAP PRODUKTIVITAS GURU MTS AN-NUQAYAH GULUK-GULUK SUMENEP - Noer Hayatie (Universitas Negeri Jakarta, 2018)
For attainment of vision, mission and mandate of the school organization, teachers’ productivity is important as well as the style of school leadership and how commitment related to the strategic issues within the organization are made. This study aims to examine the influence of (1) transformasional leadership (2) commitment, (3) teachers’ productivity in MTs An-Nuqayah Guluk-Guluk Sumenep. This quantitative research used path analysis technique in data analysis. Questionnaires were sampled to a total of 67 teachers in MTs An-Nuqayah Guluk-Guluk Sumenep using Slovin formula. The results showed that: first, there are positive influence between the transformational leadership and productivity of teachers in schools. Secondly, there is a positive effect between commitment and productivity of teachers in schools. Third , there is a positive effect between the transformational leadership and commitment in MTs An-Nuqayah Guluk-Guluk Sumenep .